Effect of cervical suspensory traction in the treatment of severe cervical kyphotic deformity - Shengfa, Pan; Hongyu, Chen; Yu, Sun; Fengshan, Zhang; Li, Zhang; Xin, Chen; Yinze, Diao; Yanbin, Zhao; Feifei, Zhou (Frontiers in Surgery, 2023)
Objective: This study aimed to investigate a new noninvasive traction method on the treatment of severe cervical kyphotic deformity. Methods: The clinical data of patients with severe cervical kyphosis (Cobb>40°)treated in Peking University Third Hospital from March 2004 to March 2020 were retrospectively summarized. 46 cases were enrolled, included 27 males and 19 females. Fifteen patients underwent skull traction and 31 patients underwent suspensory traction. Among them, 7 used combined traction after one week of suspensory traction. Bedside lateral radiograph were taken every 2 or 3 days during traction. The cervical kyphosis angle were measured on lateral radiographs in extended position at each point in time. The correction rate and evaluated Japanese Orthopedic Association (JOA) scoring for the function of spinal cord were also measured. The data before and after the operation were compared with paired sample t-test or Wilcoxon signed-rank test. Results: No neurological deterioration occurred during the skull traction and the cervical suspensory traction. There are 12 patients with normal neurological function, the JOA score of other 34 patients improved from 11.5±2.8 to 15.4±1.8 at the end of follow up(P<0.05). The average kyphotic Cobb angle was 66.1°±25.2, 28.7°±20.1 and 17.4°±25.7 pre-traction, preoperative and at the final follow-up, respectively(P<0.05). The average correction rate of skull traction and suspensory traction was 34.2% and 60.6% respectively. Among them, the correction rate of patients with simple suspensory traction was 69.3%. For patients with a correction rate of less than 40% by suspensory traction, combined traction was continued, and the correction rates after suspensory traction and combined traction were 30.7% and 67.1% respectively. Conclusions: The pre-correction by cervical suspensory traction can achieve good results for severe cervical kyphotic deformity with no wound and easy process. Combined traction is effective for supplemental traction after suspensory traction.